Prevention and treatment of pressure injuries today: literature review (Research, Society and Development, 2021)
Objective: To identify and analyze forms of prevention and treatment of LPP today. Method: This is an integrative literature review, with a quantitative approach, carried out through bibliographic surveys, using journals indexed in national databases (SCIELO, PORTAL BVS, PUBMED AND LILACS, CAPES PERIODICOS). Results: The results show that the most efficient forms of prophylaxis are a good inspection of the skin, change of position, and the use of systemic topical treatment of pressure injuries, which will consider cleaning procedures, use of primary and secondary dressings or of attachment. Conclusion: Through this proposed study, investigation of pressure injuries is expected, as well as prophylaxis and appropriate treatment.